2017
DOI: 10.1039/c7ta06995b
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt boride modified with N-doped carbon nanotubes as a high-performance bifunctional oxygen electrocatalyst

Abstract: An excellent electrocatalyst for reversible oxygen reduction and oxygen evolution synthesized by direct growth of nitrogen-doped carbon nanotubes on cobalt boride nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 53 publications
(63 reference statements)
3
52
0
Order By: Relevance
“…In addition to the activity,t he stability of ac atalyst is crucial for its technological application.T herefore, the long-term performance of the most active phase (Co 0.7 Fe 0.3 ) 2 B, was investigated using ag alvanostatic scan at ac onstant currentd ensity of 10 mA cm À2 in 1 m KOH solution ( Figure4d). [64][65][66] The observed XPS-features agree well with XPS studies of the binary Co 2 Bc atalysts by Masa et al [11,13] They also showed the transformationf rom an onactive to an activated phase after an electrochemical treatment. We assume that duringt he first two hours all sites in the networklike structure are activated leading to the highest overall catalytic performance.…”
Section: Electrochemical Characterizationsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition to the activity,t he stability of ac atalyst is crucial for its technological application.T herefore, the long-term performance of the most active phase (Co 0.7 Fe 0.3 ) 2 B, was investigated using ag alvanostatic scan at ac onstant currentd ensity of 10 mA cm À2 in 1 m KOH solution ( Figure4d). [64][65][66] The observed XPS-features agree well with XPS studies of the binary Co 2 Bc atalysts by Masa et al [11,13] They also showed the transformationf rom an onactive to an activated phase after an electrochemical treatment. We assume that duringt he first two hours all sites in the networklike structure are activated leading to the highest overall catalytic performance.…”
Section: Electrochemical Characterizationsupporting
confidence: 85%
“…[7,8]). [11][12][13] Furthermore, electrocatalytic activities of other transition-metal borides like MoB, [14] MoB 2 , [15] and Ni 3 B [16,17] are currently under investigation. [11][12][13] Furthermore, electrocatalytic activities of other transition-metal borides like MoB, [14] MoB 2 , [15] and Ni 3 B [16,17] are currently under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst powder was immobilized on a gas diffusion electrode by a spray coating technique and galvanostatically charged and discharged at ±15 mA cm −2 in a three‐electrode cell in a 6 m KOH solution as described in Ref. . The OER and ORR potentials versus number of charge/discharge cycles are presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…For example, the introduction of ORR active M‐N x /C moieties into OER‐evolving perovskites to form efficient bifunctional ORR/OER catalysts was previously demonstrated . Another example involved direct growth of N‐doped carbon nanostructures on the surface of OER‐active compounds, such as perovskites and borides by chemical vapor deposition (CVD) . The combination of ORR and OER catalysts into a composite aims at producing materials that can retain their individual properties or even slightly improve in performance owing to synergetic interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation